An improved spray-wall interaction model for Eulerian-Lagrangian simulation of liquid sprays. (January 2021) - Asgari, Behrad; Amani, Ehsan
Highlights: An improved spray-wall interaction (SWI) model is proposed. The comparison with 3 other widely-used models is presented. The present model reduces the error of spray penetration prediction to 11%. The model offers significant improvements in the prediction of all parameters studied. The effects of SWI on flow structures and drop statistics are analyzed in detail. Abstract: The focus of this research is the development of an improved spray-wall interaction (SWI) model in an Eulerian-Lagrangian framework as well as its comparison with other models mostly used in well-known computational fluid dynamics solvers, including OpenFOAM, ANSYS Fluent, and KIVA. For this purpose, first, the new model is proposed so as to avoid the inherent inconsistencies of the three previous models in determining the splashed droplet outcomes. Then, it is used for the prediction of the spray penetration radius and height of four different experimental databases. It is shown that the new model can reduce the overall error to about 11% which significantly improves the predictions compared to the other models. Finally, the evaluation against the fifth experimental database and comparison of the errors of all models prove the superiority of the improved model in predicting detailed spray, gas and droplet, statistics. The careful analysis of the results manifests that SWI has profound impacts on the gas-phase flow structures, including the wall-jet layer and vortex, near the walls due to the strong interaction of the splashed droplets with the carrier phase. On the other hand, the combination of the effects of these flow structures induces a complex variation of droplet statistics. The correct prediction of the level and trend of this variation requires the proper modeling of the splashed droplets dynamics and polydispersity which have been enhanced to a large extent by the new model.